A secure image steganography framework for covert communication using asymmetric encryption and Huffman Compression - Aulia Khamas Heikhmakhtiar; Nadiza Lediwara; Sembada Denrineksa Bimorogo (Fakultas Teknik dan Teknologi Pertahanan, Universitas Pertahanan Republik Indonesia, 2026)
This paper presents a secure data-hiding framework that combines asymmetric key cryptography, lossless data compression, and image steganography to enhance the confidentiality and imperceptibility of hidden communications. The proposed method encrypts the secret message using an asymmetric encryption scheme, compresses the resulting ciphertext using Huffman coding, and embeds the compressed data into a digital image using a spatial-domain steganographic technique. This multi-layered approach ensures that both the existence and the content of the secret message are protected. Experimental evaluations were conducted using standard image quality metrics, including Mean Squared Error (MSE), Peak Signal-to-Noise Ratio (PSNR), and Structural Similarity Index Measure (SSIM), to assess visual imperceptibility, along with performance analysis to evaluate computational overhead. The results demonstrate that the proposed method achieves high image quality with minimal distortion while maintaining strong cryptographic security. The integration of compression effectively reduces embedding payload, further improving steganographic performance. The findings indicate that the proposed framework provides a robust and practical solution for secure and covert data transmission.